CHANGES IN THE CONSTRUCTION INDUSTRY IN 2021-2025 AND THE ROLE AND ROLE OF CONSTRUCTION IN THE ECONOMY OF OUR COUNTRY (International Conference on Medical Science, Medicine and Public Health, 2025)
This article examines the role and importance of the construction industry in the national economy of our country today. Maintaining the high rates of economic growth outlined by our president is also closely linked to ongoing reforms in the construction sector, and data on the implementation of construction works in the Republic of Uzbekistan by the statistics Department is also provided.